Accuracy of Direct Microscopy in Early Diagnosis of Fungal Keratitis using Potassium Hydroxide - Muhammad All Shar, Khan Muhammad Nangrejo, Attaullah Shah Bukhari, Shahid Jamal Siddiqui, All Muhammad Abbas!, Liaquat Ali Shah, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To determine the accuracy of direct microscopy in early diagnosis of fungal keratitis using potassium hydroxide. Methods: This cross sectional study was conducted in the department of Ophthalmology at Peoples University of Medical & Health Sciences for Women Nawabshah District Shaheed Benazirabad and Khairpur Medical College Khairpur Mirs, Sindh, from 1" January 2016 to 306 June 2016. This study included 200 patients, from Two Health Centers on daily basis enrolled by convenience sampling method having clinical diagnosis of fungal keratitis through eye OPD. After considering inclusion and exclusion criteria the patients were divided into two groups A and B, each containing 100 patients, Results: 200 Patients had mean age of 37.25 13.87 Years. 121 (60.5%) were males while 79 (39.5%) were females with male to female ratio of 1.4:1. Mostly the age range affected was 31 to 50 years, 83 (41.5%), 15-30 years 69 (34,5%) patients and 51 to 70 years 48 (24%) patients respectively. Out of 100 patient of group A, who was started topical antifungal without scraping & stain 56 (56%) patients responded and fulfilled the improvement criteria at the end of 41' week. In group B out of 100, 71 (71%) patients stained positive with potassium hydro oxide (KOH) stain on scrape material. These 71 patients were started with topical antifungal and 65 (91.54%) patients responded and fulfilled the improvement criteria at the end ofe week. Conclusion: Direct microscopy with 1(01-I stain is very much useful with regard to accuracy for the suspected cases of fungal keratitis which is a preventable cause of blindness in corneal ulcers. It is therefore beneficial in early detection and management of keratitis.